2020
DOI: 10.1177/1120672120960332
|View full text |Cite
|
Sign up to set email alerts
|

The Alberta standardized orbital technique in the management of spheno-orbital meningiomas

Abstract: Purpose: To describe a standardized orbital resection technique and outcomes for spheno-orbital meningiomas with soft-tissue invasion of the orbit. Methods: A retrospective case review of patients with spheno-orbital meningioma that underwent resection utilizing the Alberta Standardized Orbital Technique (ASOT) between 2008 and 2017 was performed. Results: Twenty patients met the inclusion criteria. Fifteen females and five males, with an average age of 53.4 years (SD ± 13.1 years). Mean follow-up was 57.3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Radiographic studies to assess for recurrence should be considered postoperatively each 6 months for 2 years and yearly thereafter. 9 However, as was the case for our patient, CNS WHO grade 3 SOMs carry a poor prognosis for survival.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Radiographic studies to assess for recurrence should be considered postoperatively each 6 months for 2 years and yearly thereafter. 9 However, as was the case for our patient, CNS WHO grade 3 SOMs carry a poor prognosis for survival.…”
supporting
confidence: 67%
“…6 The primary treatment for anaplastic meningiomas is gross total surgical resection and adjuvant radiation. 9 The literature on chemotherapy is not yet conclusive. Resection of the orbital component of SOMs necessitates a multidisciplinary team including both neurosurgeons and orbital surgeons.…”
mentioning
confidence: 99%
“…When considering only WHO grade I SOM, a Ki67 index ≥3.3 is associated with a higher risk of recurrence. Comparing these different histological subgroups, Agi et al reported a recurrence rate of 22% in the WHO grade I tumors and 50% in the WHO grade II tumors, with a mean follow-up of 57 months [46].…”
Section: Oncological Outcomementioning
confidence: 99%